2020
DOI: 10.34133/2020/5839856
|View full text |Cite
|
Sign up to set email alerts
|

“Macrobot”: An Automated Segmentation-Based System for Powdery Mildew Disease Quantification

Abstract: Managing plant diseases is increasingly difficult due to reasons such as intensifying the field production, climatic change-driven expansion of pests, redraw and loss of effectiveness of pesticides, rapid breakdown of the disease resistance in the field, and other factors. The substantial progress in genomics of both plants and pathogens, achieved in the last decades, has the potential to counteract this negative trend, however, only when the genomic data is supported by relevant phenotypic data that allows li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…All RILs, the parental lines, and the susceptible standard “Akteur” were evaluated for resistance at the seedling stage in a detached leaf assay (Lück et al, 2020 ). Seedlings were grown in 77-cell propagation trays with mixed potting soil (Gebr.…”
Section: Methodsmentioning
confidence: 99%
“…All RILs, the parental lines, and the susceptible standard “Akteur” were evaluated for resistance at the seedling stage in a detached leaf assay (Lück et al, 2020 ). Seedlings were grown in 77-cell propagation trays with mixed potting soil (Gebr.…”
Section: Methodsmentioning
confidence: 99%
“…The relation between leaf size and pustule size resulted in the rated percentage of infected leaf area [28]. A more detailed description of the experimental setup can be found elsewhere [23].…”
Section: Evaluating Leaf Rust Resistance In Greenhouse Experimentsmentioning
confidence: 99%
“…Therefore, the development of pioneering phenotyping strategies is requested to generate highly precise data in a time-and resource-saving manner [20]. Some strategies fulfilling these issues have already been published on the basis of greenhouse trials [23,24]. For instance, Lueck et al (2020) [23] reported a highly promising approach by generating detached leaf assays of seedlings screened by a robotic-and computer-based, high-throughput system (further denoted as Macrobot platform).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For reviews on this topic see [6,7,28,29]. For visually easily detectable diseases located on the leaf surface like powdery mildew several deep learning image segmentation approaches have been published in recent years [24,30,31].…”
Section: Discussionmentioning
confidence: 99%